Mechanochemical Preparation, Characterization and Biological Activity of Stable CuS Nanosuspension Capped by Bovine Serum Albumin - Stahorský, Martin; Lukáčová Bujňáková, Zdenka; Dutková, Erika; Kello, Martin; Mahlovanyi, Bohdan; Shpotyuk, Yaroslav; Daneu, Nina; Trajić, Jelena; Baláž, Matej (Frontiers in Chemistry, 2022)
The biocompatible nanosuspension of CuS nanoparticles (NPs) using bovine serum albumin (BSA) as a capping agent was prepared using a two-stage mechanochemical approach. CuS NPs were firstly synthetized by a high-energy planetary ball milling in 15 minutes by milling elemental precursors. The stability of nanoparticles in the simulated body fluids was studied, revealing zero copper concentration in the leachates, except simulated lung fluid (SLF, 0.015%) and simulated gastric fluid (SGF, 0.078%). Albumin sorption on CuS NPs was studied in static and dynamic modes showing a higher kinetic rate for the dynamic mode when the equilibrium state of adsorption was reached after 90 minutes with an adsorption capacity of 86 mg/g compared to the static mode when the capacity 59 mg/g was reached after 2 hours. Then, a wet stirred media milling in a solution of BSA was introduced to yield the CuS-BSA nanosuspension, being stable for more than 10 months, as confirmed by photon cross-correlation spectroscopy. The fluorescent properties of the nanosuspension were confirmed by photoluminescence spectroscopy, which also showed that tryptophan present in the BSA could be closer to the binding site of CuS than the tyrosine residue. The dried nanosuspension contained a large amount of NaCl, as a result of using the phosphate buffer solution. NaCl content was much more significant than that of CuS, as the centrifugation has led to a decrease in the content of the latter. The purification from NaCl has shown that part of CuS is also present in XRD-amorphous structure. The biological activity was determined by in vitro tests on selected cancer and non-tumor cell lines. The results have shown that the CuS-BSA nanosuspension inhibits the metabolic activity of the cells as well as decreases their viability upon photothermal ablation.